The molecular structure and multifunctionality of the cryptic plant polymer suberin. (January 2020) - Correia, V.G.; Bento, A.; Pais, J.; Rodrigues, R.; Haliński, Ł.P.; Frydrych, M.; Greenhalgh, A.; Stepnowski, P.; Vollrath, F.; King, A.W.T.; Silva Pereira, C.
Abstract: Suberin, a plant polyester, consists of polyfunctional long-chain fatty acids and glycerol and is an intriguing candidate as a novel antimicrobial material. We purified suberin from cork using ionic-liquid catalysis during which the glycerol bonds that ensure the polymeric nature of suberin remained intact or were only partially cleaved—yielding the closest to a native configuration reported to date. The chemistry of suberin, both in situ (in cryogenically ground cork) and ex situ (ionic-liquid extracted), was elucidated using high-resolution one- and two-dimensional solution-state NMR analyses. Centrifugation was used to isolate suberin particles of distinct densities and their monomeric composition, assembly, and bactericidal effect, inter alia, were assessed. Analysis of the molecular structure of suberin revealed the relative abundance of linear aliphatic vs. acylglycerol esters, comprising all acylglycerol configurations and the amounts of total carbonyls (CO), free acid end groups (COOH), OH aliphatics, and OH aromatics. Suberin centrifuged fractions revealed generic physiochemical properties and monomeric composition ​and self-assemble into polygonal structures that display distinct degrees of compactness when lyophilized. Suberin particles— suberinsomes —display bactericidal activity against major human pathogenic bacteria. Fingerprinting the multifunctionality of complex (plant) polyesters such as suberin allows for the identification of novel polymer assemblies with significant value-added properties. Graphical abstract: Image 1